A digital “flat affect”? Popular speech compression codecs and their effects on emotional prosody - Niebuhr, Oliver; Siegert, Ingo (Frontiers in Communication, 2023)
Calls via video apps, mobile phones and similar digital channels are a rapidly growing form of speech communication. Such calls are not only – and perhaps less and less – about exchanging content, but about creating, maintaining, and expanding social and business networks. In the phonetic code of speech, these social and emotional signals are considerably shaped by (or encoded in) prosody. However, according to previous studies, it is precisely this prosody that is significantly distorted by modern compression codecs. As a result, the identification of emotions becomes blurred and can even be lost to the extent that opposing emotions like joy and anger or disgust and sadness are no longer differentiated on the recipients’ side. The present study searches for the acoustic origins of these perceptual findings, based on 108 sentences from the Berlin Database of Emotional Speech. The sentences were realized by professional actors (2m, 2f) with seven different emotions and acoustically analyzed in the original (WAV) version and in strongly compressed versions based on the four popular codecs AMR-WB, MP3, OPUS, and SPEEX. The analysis included 6 tonal and 7 non-tonal prosodic parameters. Results show significant, codec-specific distortion effects on all 13 prosodic parameter measurements compared to the WAV reference condition. The effects increase the tonal acoustic differences between emotions, but decrease the non-tonal ones, particularly for MP3 and SPEEX. The results are discussed in view of their generalizability and, in this context, with regard to practical implications and further research perspectives.